Microscopic and molecular identification of hemotropic mycoplasmas in South American coatis (Nasua nasua). (August 2017) - Cubilla, Michelle P.; Santos, Leonilda C.; de Moraes, Wanderlei; Cubas, Zalmir S.; Leutenegger, Christian M.; Estrada, Marko; Lindsay, LeAnn L.; Trindade, Edvaldo S.; Franco, Célia Regina C.; Vieira, Rafael F.C.; Biondo, Alexander W.; Sykes, Jane E.
Highlights: Hemoplasma was detected in Nasua nasua by three different techniques for microscopy. Sequencing confirmed organisms resembling M. haemofelis and Mycoplasma sp. Potential risk of transmission to human beings, domestic and wild animals. Abstract: Hemoplasmas were detected in two apparently healthy captive South American coatis ( Nasua nasua ) from southern Brazil during an investigation for vector-borne pathogens. Blood was subjected to packed cell volume (PCV) determination, a commercial real-time PCR panel for the detection of Anaplasma spp., Babesia spp., Bartonella spp., Hepatozoon spp., Leishmania spp., Mycoplasma haemofelis, ' Candidatus Mycoplasma turicensis', ' Candidatus Mycoplasma haemominutum', Neorickettsia risticii, Rickettsia rickettsii and Leptospira spp., and a pan-hemoplasma conventional PCR assay. PCV was normal, but both coatis tested positive for hemoplasmas and negative for all the remaining pathogens tested. Using different techniques for microscopy (light, confocal or SEM), structures compatible with hemoplasmas were identified. Sequencing of the 16S rRNA gene identified an organism resembling Mycoplasma haemofelis and another hemotropic Mycoplasma sp., with a sequence identity of 96.8% to a Mycoplasma sp. previously detected in capybaras.